THE ROLE OF THERAPEUTIC PRACTICE IN THE DIAGNOSIS OF INTERNAL DISEASES: AN INTEGRATED APPROACH TO CLINICAL DECISION-MAKING - Vokhidjon Khatamov (Web of Journals Publishing, 2025)
Therapeutic practice plays a pivotal role in the diagnosis and management of internal diseases by serving as a bridge between clinical observation and evidence-based decision-making. As internal diseases often present with complex, overlapping symptoms, a comprehensive therapeutic approach enables clinicians to refine diagnostic accuracy through continuous patient assessment, response monitoring, and interdisciplinary collaboration. This article explores how therapeutic strategies not only support symptom control and disease management but also contribute directly to diagnostic clarification through individualized treatment responses and functional evaluations. By emphasizing a holistic, patient-centered model, this paper advocates for the integration of therapeutic insights into diagnostic pathways, highlighting their value in improving clinical outcomes, enhancing patient satisfaction, and fostering more precise and timely medical decisions
Keywords: Therapeutic practice; internal diseases; clinical diagnosis; integrated approach; patient-centered care; diagnostic strategy; evidence-based medicine; interdisciplinary collaboration; clinical decision-making; functional assessment.